Eksistensi Lembaga Lingkungan Hidup Internasional dalam Pengelolaan Lingkungan Hidup - Candra, Gita Ayu Sartika (HK-Publishing, 2022)
This study aims to examine the role and position of international environmental institutions in environmental management. Environmental issues are international issues that have a broad effect, involving the exploitation of global resources such as the oceans and atmosphere, as well as the existence of transnational environmental destruction. The United Nations Environment Program (UNEP) is a United Nations (UN) environmental agency that specifically deals with global environmental problems by actively promoting the enforcement of sustainable development in the world. The research method used in this paper is a descriptive analysis method with a historical approach and a conceptual approach. The results of this study indicate that the United Nations through UNEP is able to emphasize government policies in environmental protection programs globally.